Exchanging Information on Road Traffic Offences: A Measure of Police Cooperation or Transport Policy? Case Note on C-43/12 Commission v Parliament and Council. Issue 1 (March 2016) - Vavoula, Niovi
The present case note examines the judgment of the CJEU concerning the legal basis of an EU instrument establishing an information exchange system for road-traffic offences (C-43/12 Commission v Parliament and Council). The case arose from the interinstitutional battle between the Commission on the one hand and the Parliament and Council on the other, whereby the former considered that such a scheme forms part of the EU transport policy, while the latter opined that it constitutes a standard police cooperation measure. In this context, this case note maps the historical background behind the case from the release of proposal for a directive by the Commission to the adoption of a Framework Decision instead and the institution of infringement proceedings before the CJEU. Then, the conflicting opinions of the parties, the Advocate General and the Grand Chamber are analysed, followed by commentary.